1998
DOI: 10.1046/j.1365-2265.1998.3611177.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in acromegalic patients: clinical measurement versus 24-hour ambulatory blood pressure monitoring

Abstract: Ambulatory blood-pressure monitoring indicated a lower prevalence of hypertension in acromegalic patients then usually reported, suggesting that the role of hypertension in the pathogenesis of acromegalic cardiomyopathy is commonly overestimated. We propose that ambulatory blood-pressure monitoring should be routinely proposed in acromegalics with high or borderline clinical blood pressure values although it is not useful in patients defined normotensive according to repeated clinical measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
1
12
0
4
Order By: Relevance
“…No correlation was found between BP values and either patients BMI or IRI, GH and IGF-I levels. The lack of correlation between GH/IGF-I values and BP values is in agreement with most studies (Kraatz et al, 1990;Ezzat et al, 1994;Minniti et al, 1998b;Colao et al 2000), although higher GH values were found in hypertensive acromegalics in a single report (Ikeda et al, 1993). Neither did the appearent duration of disease, which has been reported to contribute to myocardial performance impairement in acromegalics (Colao et al, 1999), correlate with either BP values or glucose tolerance in this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…No correlation was found between BP values and either patients BMI or IRI, GH and IGF-I levels. The lack of correlation between GH/IGF-I values and BP values is in agreement with most studies (Kraatz et al, 1990;Ezzat et al, 1994;Minniti et al, 1998b;Colao et al 2000), although higher GH values were found in hypertensive acromegalics in a single report (Ikeda et al, 1993). Neither did the appearent duration of disease, which has been reported to contribute to myocardial performance impairement in acromegalics (Colao et al, 1999), correlate with either BP values or glucose tolerance in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The main advantages of 24-h ABPM over clinical measurement are to disclose high occasional BP values due to the`white-coat effect' and to provide additional information concerning nocturnal BP values (Mallion et al, 1999). Using 24-h BP values for the definition of systemic hypertension instead of clinical BP measurement (Staessen et al, 1993) may lead to significant differences in its appearent prevalence (Minniti et al, 1998b), and recent recommendations of JNC (1997) suggest to more clearly distinguish between diurnal BP values ± which circumvent the`white-coat effect' ± and nocturnal BP values. In the present series, the prevalence of high diurnal BP values was 47´0%, with a progressive increase from 30´8% in patients with NGT patients to 76´9% in patients with DM, a similar trend being observed for clinical and nocturnal BP values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Hypertension affects approximately one-third of patients with acromegaly, with values ranging from 17·5% to 57% in different series. [6][7][8][9][10][11][12][13][14][15][16] In a recent epidemiological study, hypertension was found in 39·1% of 1036 cases reported. 17 In a case-control study including 200 patients with acromegaly, Vitale et al .…”
Section: Introductionmentioning
confidence: 99%